Penerapan model pembelajaran problem solving fisika berbantuan alat peraga kolektor surya pada pembelajaran kalor di SMA IT Iqra’ - Rini Wulandari; Eko Swistoro; M Lutfi Firdaus (University of Bengkulu, 2019)
AbstraCT[Application of Physics Problem Solving Learning Model Assisted Collector Solar Props on Heat Learning in SMA IT Iqra ']. The aims of this study is to explain the students 'cognitive learning outcomes using the learning model of Physics Solving Problem assisted solar collectors in heat learning in SMA IT Iqra' Bengkulu, and to explain the cognitive learning outcomes between high, medium and low group students. The subjects of this study are 24 students who follow the physical extracurricular activities in SMA IT Iqra ' Bengkulu. This type of research is pre-experimental by setting aside a group of pretest and posttest designs. Student cognitive learning result data obtained by test instrument that is question of multiple choice. Pretest measurement data form the basis for grouping students into high, medium and low groups. Data on cognitive learning outcomes were analyzed and calculated using normalized gain values and analyzed using the Anova test. The results showed that overall N-gain of 0.59 was moderate. N-gain based on group that is high group equal to 0,72; medium group of 0,58; and low group of 0.47. Based on anova test conducted to know the difference of cognitive learning result between student group obtained Fcount = 4,046 > F table 3,47 and sig value. 0.033 ? 0.05. The conclusion of this research is the learning model of Physics Solving Problem assisted by solar collector can improve students 'cognitive learning outcomes in extracurricular activities in SMA IT Iqra' Bengkulu and there is a significant difference of cognitive learning achievement among high, medium and low students.Keywords: Learning model; Physics Problem Solving; Heat, Cognitive learning outcomes (Received December 17, 2019; Accepted July 5, 2019; Published October 24, 2019) AbstrakPenelitian ini bertujuan untuk menjelaskan peningkatan hasil belajar kognitif siswa yang diajarkan menggunakan model pembelajaran Problem Solving Fisika berbantuan alat peraga kolektor surya dalam pembelajaran kalor di SMA IT Iqra’ Kota Bengkulu, dan untuk menjelaskan perbedaan peningkatan hasil belajar kognitif antara siswa kelompok tinggi, sedang dan rendah. Subjek penelitian ini adalah 24 siswa yang mengikuti kegiatan ekstrakurikuler fisika di SMA IT Iqra’ Kota Bengkulu. Jenis penelitian adalah pre-eksperimental dengan desain one group pretest and posttest design. Data hasil belajar kognitif siswa diperoleh dengan instrumen tes yaitu soal pilihan ganda. Data hasil nilai pretest menjadi dasar pengelompokan siswa ke dalam kelompok tinggi, sedang dan rendah . Data hasil belajar kognitif dianalisis secara deskriptif dan dihitung dengan menggunakan skor gain yang dinormalisasi serta dianalisis menggunakan uji Anova. Hasil penelitian menunjukkan N-gain keseluruhan siswa sebesar 0,59 berkategori sedang. N-gain berdasarkan kelompok yaitu kelompok tinggi sebesar 0,72; kelompok sedang sebesar 0,58; dan kelompok rendah sebesar 0,47. Berdasarkan uji anova yang dilakukan untuk mengetahui perbedaan hasil belajar kognitif antar kelompok siswa diperoleh Fhitung 4,046 > Ftabel 3,47 dan nilai sig. 0,033 ? 0.05. Kesimpulan penelitian ini adalah model pembelajaran Problem Solving Fisika berbantuan alat peraga kolektor surya dapat meningkatkan hasil belajar kognitif siswa pada kegiatan ekstrakurikuler di SMA IT Iqra’ Kota Bengkulu dan terdapat perbedaan peningkatan hasil belajar kognitif yang signifikan antara siswa kelompok tinggi, sedang dan rendah.Kata kunci: Model Pembelajaran; Problem Solving Fisika; Kalor, Hasil belajar kognitif.